Upper Limb Muscle Activity among Workers in Large-Herd Industrialized Dairy Operations - Mixco, Anthony; Masci, Federica; Brents, Colleen Annika; Rosecrance, John (Frontiers in Public Health, 2016)
Objectives: The primary aim of this cross-sectional research study was to quantify upper limb muscle activity among workers performing milking tasks in large-herd dairy parlors. Methods: Surface electromyography (sEMG) from the trapezius, anterior deltoid, biceps brachii, wrist flexors and wrist extensors muscles of 26 dairy workers were used to create muscle activity profiles for the milking tasks common in large-herd dairy parlors. Functional maximum voluntary contractions (fMVC) were collected to normalize the sEMG data for appropriate comparisons. Anthropometric measurements were recorded from each worker. Results: The biceps brachii had the highest muscle activity (14.58 %f MVC) of the upper limb muscles measured, exceeding previously established recommendations for working tasks. The anterior deltoid had the least amount of activity while the upper trapezius had the least amount of muscular rest during milking work. Worker stature was negatively associated with upper limb muscle activity. Conclusions: Milking tasks in large-herd dairy parlors have significant effects on the upper limb muscle activity of workers. The muscle activity of biceps brachii during normal work tasks exceeded the recommended safe limit. Wrist flexors and upper trapezius approached the recommended limit. The study findings suggest that milking tasks in large-herd dairies may increase the worker’s risk for developing musculoskeletal symptoms and possibly MSDs.